Risk Factors for Neovascular Glaucoma in Patients with Central Retinal Vein Occlussion: A Systematic Review and Meta-analysis - Faadhil, Muhammad Arsy Kamal; Yusran, Muhammad (Jurnal Medika Malahayati, 2025)
Neovascular Glaucoma (NVG) is a serious complication of Central Retinal Vein Occlusion (CRVO). This study evaluates the relationship between CRVO and NVG to understand prevalence and contributing risk factors. A PROSPERO-registered protocol (CRD42024588660) guided the systematic review and meta-analysis. Searches in PubMed, Cochrane Library, and Scopus identified studies on CRVO and NVG. Eligible studies were assessed using the ROBBINS-I risk of bias tool. Out of 203 studies, three met the criteria, with older age and ischemic CRVO identified as key factors for NVG development. Ischemic CRVO was the strongest predictor (RR: 4.37; 95% CI: 2.18–8.76; p0.0001), followed by older age (mean difference: 6.24; 95% CI: 1.50–12.51; p=0.010). Elevated intraocular pressure (IOP) also showed relevance (mean difference: 1.74; 95% CI: 0.45–3.02; p=0.008), though study heterogeneity limited interpretation. Additional risks included subretinal fluid and poor baseline visual acuity, while systemic conditions like hypertension (RR: 1.41; 95% CI: 0.63–3.12; p=0.40) and diabetes (RR: 1.94; 95% CI: 0.95–3.96; p=0.07) showed weaker associations. Gender was not significantly associated with NVG risk (RR: 0.95; 95% CI: 0.47–1.96; p=0.90). NVG in CRVO patients is strongly associated with ischemic CRVO and older age.